Influence of sector coupling on a district heating system in a German town: thermal simulation and comparison of different supply scenarios - Vallese, Laura; Wett, Lina; De Carli, Michele; Cadenbach, Anna Marie (International Journal of Sustainable Energy Planning and Management, 2026)
District heating grids (DHGs) offer substantial potential for decarbonising the heating sector, which accounts for around 40% of Europe’s total energy consumption. Although DHGs are a mature technology, the integration of renewable energy (RE) remains limited. This study evaluates Hybrid Network Solutions (HNS) through a one-year simulation of three heat supply scenarios in a southern German town. Two innovative HNS concepts incorporate rooftop photovoltaic (PV) systems and decentralised thermal energy storage (TES) to enable sector coupling via electric heating elements and air-to-water heat pumps (HPs). Scenario 1 integrates heat supply through a DHG with decentralised Power-to-Heat (P2H) units, enabling greenhouse gas (GHG) reductions by utilizing surplus PV electricity. Scenario two introduces a dual-grid structure with a low-temperature network supplied by a large groundwater heat pump and a high-temperature DHG using waste heat. While this configuration reduces final energy demand, it results in higher GHG emissions due to reliance on grid electricity with a high primary energy factor. The findings highlight the efficiency potential of HPs and the importance of aligning heat sector electrification with power sector decarbonisation. HNS concepts can serve as scalable models for sustainable district heating, provided that a renewable electricity supply and intelligent operational strategies are ensured.